The putative oncogene CEP72 inhibits the mitotic function of BRCA1 and induces chromosomal instability - Lüddecke, Sina; Stenzinger, Albrecht; Weichert, Wilko (Oncogene, 2016)
BRCA1 is a tumor-suppressor gene associated with, but not restricted to, breast and ovarian cancer and implicated in various biological functions. During mitosis, BRCA1 and its positive regulator Chk2 are localized at centrosomes and are required for the regulation of microtubule plus end assembly, thereby ensuring faithful mitosis and numerical chromosome stability. However, the function of BRCA1 during mitosis has not been defined mechanistically. To gain insights into the mitotic role of BRCA1 in regulating microtubule assembly, we systematically identified proteins interacting with BRCA1 during mitosis and found the centrosomal protein Cep72 as a novel BRCA1-interacting protein. CEP72 is frequently upregulated in colorectal cancer tissues and overexpression of CEP72 mirrors the consequences of BRCA1 loss during mitosis. In detail, the overexpression of CEP72 causes an increase in microtubule plus end assembly, abnormal mitotic spindle formation and the induction of chromosomal instability. Moreover, we show that high levels of Cep72 counteract Chk2 as a positive regulator of BRCA1 to ensure proper mitotic microtubule assembly. Thus, CEP72 represents a putative oncogene in colorectal cancer that might negatively regulate the mitotic function of BRCA1 to ensure chromosomal stability.
Published: 24 August 2015
Gesehen am 12.09.2019
Im titel ist "CEP72" kursiv geschrieben